Realization of the File Format Processing System for LKJ Running Record Data - 杨献; 言圣 (机车电传动)
This paper introduces the realization of file format processing system for LKJ running record data, mainly focused on system composition, system function, system realization and system running condition. The processing and display of LKJ running record data file can be specified by the module application of file format processing system for LKJ running record data. At the same time, the core module of LKJ running record data system can be shared.